Survey of health monitoring programmes from laboratory animal facilities in India (Journal of Laboratory Animal Science, 2024)
Health monitoring in laboratory animals provides health status of the colony and helps in providing clean animals which  plays a pivotal role in the outcome of the experimental results. The assessment of microbial status of the laboratory animals  is considered as part of the animal care program. The primary objectives of the survey included were as follows: a) To  understand the health status of the animals and health monitoring programs in India, b) To create a platform to share the  ideas and practices followed among the laboratory animal care professionals, c) To provide solution to uplift the standards  of these programs. The institutions that participated in this program were approved by the Committee for the Purpose of  Control and Supervision on Experiments on Animals (CPCSEA) and some of them certified by Good Laboratory Practice  (GLP) of the National GLP Compliance Monitoring Authority of Dept.of Science and Technology, Association for the  Assessment and Accreditation of Laboratory Animal Care International (AAALAC) and National Accreditation Board  for Testing and Calibration Laboratories (NABL). The response from each institution was obtained unanimously and the  compiled results were maintained confidentially prior to disclosure in an appropriate forum. The responses showed that  most of the institutions were following health monitoring programs and are required to harmonize testing methods and  frequency based on the duration of experiments as well as the integrity of the facility.
Keywords: Health monitoring survey; sentinel program; rodent diseases; diagnostic methods; sanitation practices